1982
DOI: 10.1002/anie.198200762
|View full text |Cite
|
Sign up to set email alerts
|

Oxanickelacyclopentene Derivatives from Nickel(0), Carbon Dioxide, and Alkynes

Abstract: The complete manuscript of this communication appears in: Angew. Chem. Suppl. 1982, 147. DOI:10.1002/anie.198201470

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 3 publications
0
39
0
Order By: Relevance
“…During the first half of the 1980s, Hoberg and co-workers were able -among others -to demonstrate various oxidative couplings between CO 2 and alkenes [36,37], dienes [38,39], alkynes [40][41][42], and allenes [43], leading to a deeper understanding of the elementary steps involved in these processes. For example, it was revealed that a very common pathway of CO 2 activation at Ni(0) metal centers proceeds via the formation of five-memberedring nickelalactones.…”
Section: Reactions With Group 10 Metalsmentioning
confidence: 99%
“…During the first half of the 1980s, Hoberg and co-workers were able -among others -to demonstrate various oxidative couplings between CO 2 and alkenes [36,37], dienes [38,39], alkynes [40][41][42], and allenes [43], leading to a deeper understanding of the elementary steps involved in these processes. For example, it was revealed that a very common pathway of CO 2 activation at Ni(0) metal centers proceeds via the formation of five-memberedring nickelalactones.…”
Section: Reactions With Group 10 Metalsmentioning
confidence: 99%
“…Prompted by the seminal Ni-catalyzed oxidative cyclization work of Inoue for preparing 2-pyrones using CO 2 as coupling partner [30], Burkhart and Hoberg reported the isolation of an oxanickelacyclopentene (nickelalactone) from the coupling of 2-butyne and CO 2 with Ni(cdt) (cdt = 1,5,6-cyclododecatriene) and N,N,N',N'-tetramethylethylenediamine (TMEDA) [31]. The authors highlighted that the corresponding α,β-unsaturated carboxylic acid can be easily within reach upon simple protonolysis (Scheme 1).…”
Section: Stoichiometric Processesmentioning
confidence: 99%
“…The first metal-catalyzed carboxylation of alkynes with CO 2 was reported three years before the isolation of nickelalactones by Hoberg [31]. Specifically, in 1977 Inoue described the carboxylation of alkynes with CO 2 leading to the formation of 2-pyrones.…”
Section: Catalytic Carboxylation Of Alkynesmentioning
confidence: 99%
“…In the following years a lot of work was devoted to the oxidative coupling of CO 2 with olefins at nickel complexes [38] by many groups, with detailed fundamental knowledge resulting from the systematic work by Hoberg [62]. The nickelalactones undergo hydrolysis in the presence of mineral acids leading to the degradation of the nickel complex and formation of the free acrylic acid in a stoichiometric reaction.…”
Section: Oxidative Coupling Of Co 2 and Olefinsmetallalactones As Intmentioning
confidence: 99%